Hollywood musicals - Cohan, Steven, 1948- (Routledge film guidebooks, 2020)
"Hollywood Musicals offers an insightful account of a genre that was once a mainstay of 20th century film production and continues to draw audiences today. What is a film musical? How do musicals work, formally and culturally? Why have they endured since the introduction of sound in the late 1920s? How are they more than glittery surfaces or escapist fare? Highlights include extended discussions of such celebrated musicals from the studio era as The Love Parade, Top Hat, Holiday Inn, Stormy Weather, The Gang's All Here, Meet Me in St. Louis, Cover Girl, Mother Wore Tights, Singin' in the Rain, Gentlemen Prefer Blondes, The Band Wagon, Seven Brides for Seven Brothers, and Jailhouse Rock as well as later films, such as Cabaret, All that Jazz, Beauty and the Beast, and La La Land."--